MARKETING COMMUNICATION STRATEGY MAHRATU FOUNDATION IN PROMOTE TENUNAN SONGKET PEKANBARU - Sri Bintan Laksamana; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru city is one of destination for tourism, business, jobs and residences by the people around Pekanbaru region. Due to its cultures and diversity of community, Pekanbaru has many kind of arts and handicrafts which has high economic value. One of the famous handicrafts in Riau Province, especially in Pekanbaru is Tenunan Songket Pekanbaru. Tenunan Songket Pekanbaru itself has always been used by the people for traditional event, weddings, cultural events, religious events and others. Based on sales recapitulation data of Tenunan Songket Pekanbaru by Mahratu Foundation from January 2012 to Desember 2013, shown that sales of Tenunan Songket Pekanbaru decreased every month and still could not reached sales target. The data also indicated that there were 12 months no sales activities among the total of 24 months surveillance. This research aimed to know: (1) strategy of marketing communication Mahratu Foundation in promote Tenunan Songket Pekanbaru (2) Supporting and inhibiting factors of marketing Mahratu Foundation in promote Tenunan Songket Pekanbaru. The method used in this research is qualitative method with analytical representation descriptive. This data collecting tech is acquired matter-of-fact that happening at field via observation, interview and documentation. Informan in observational it total 9 person, one that consisting of (Mahratu Foundation chairman, 1 Foundation secretariat Employee Mahratu, 1 Gallery Employee Songket, 1 Weave Production Coordinator Songket Mahratu Foundation, and 5 customers). The research conducted in Mahratu Foundation Pekanbaru located in Jl. Thamrin V Number 3 Pekanbaru, Riau Province. Analysis tech data that is utilized in this research it utilizes analisis's model Milles's interactive data and Haberman, by use of authenticity check tech data which is participation and triangulation. These results it was shown that the strategy of marketing communication Mahratu Foundation in promote Tenunan Songket Pekanbaru has not fully implemented the 5 mix promotion concept of Philip Kotler’s which consist of Advertising, Sales Promotion, Personal Selling, Public Relation and Direct Marketing. Mahratu Foundation applied Personal Selling, Public Relation and Direct Marketing. Marketing communication model that has been used by Mahratu Foundation has not fully applied in accordance to AIDDA Marketing Model to raising (Awareness, Attention, Desire, Decision and Action). Keywords: Strategy, Marketing Communication, Promote.